Analisis Indeks Kualitas Tanah pada Tipe Penggunaan Lahan Berbeda di Kecamatan Maginti - Jumiun, Sri; Darwis, Darwis; Namriah, Namriah; Ginting, Sahta; Leomo, Sitti; Zulfikar, Zulfikar (Universitas Ma'arif Nahdlatul Ulama Kebumen, 2024)
Soil quality is the ability of the soil to function to maintain plant productivity, maintain and maintain water availability and support human activities. The purpose of this study was to determine the Soil Quality Index (SQI) and determine the management direction for improving soil quality on different land uses in the Maginti sub-district. A field study and laboratory analysis were carried out from March to May 2022. The method used in this study was a free survey method through field observations conducted on 2 types of land use, namely irrigated rice fields and dry land. In irrigated rice fields, 3 sample points were taken and 3 sample points in dry land, then composited into 1 sample in order to represent the total amount of each land use. In calculating the value of the soil quality index using the formula by Bajracharya (2006) which has been modified by Ghimire (2018). The soil quality index is analyzed using the indicators that best represent soil functions. The variables observed included Texture, pH, C-Organic, N-Total, P-Available and K-Available. Soil quality index values range from 0-1, the higher the index value, the better the quality. The results of the analysis of the selected soil functions (minimum data set/MDS) and the MDS scoring were summed to determine the value of the soil quality index (SQI). The conclusion of this research is that the criteria for medium soil quality are irrigated rice fields with SQI (0,56) and dry land with low criteria with SQI (0,36). To improve soil quality in irrigated paddy fields and dry lands is to increase organic matter through the application of organic fertilizers with the right dosage according to the type and level of soil fertility.Keywords: Soil Quality Index, Irrigated Rice Fields, Non-Irrigation, Soil Management, Physical Properties of Soil Chemistry.